In the Spirit of a New People : The Cultural Politics of the Chicano Movement - Ontiveros, Randy J. (Book collections on Project MUSE., 2014)
Reexamining the Chicano civil rights movement of the 1960s and 1970s, this book brings to light new insights about social activism in the twentieth-century and new lessons for progressive politics in the twenty-first. The author explores the ways in which Chicano/a artists and activists used fiction, poetry, visual arts, theater, and other expressive forms to forge a common purpose and to challenge inequality in America. Focusing on cultural politics, this book reveals neglected stories about the Chicano movement and its impact: how writers used the street press to push back against the network news; how visual artists such as Santa Barraza used painting, installations, and mixed media to challenge racism in mainstream environmentalism; how El Teatro Campesino's innovative "actos," or short skits, sought to embody new, more inclusive forms of citizenship; and how Sandra Cisneros and other Chicana novelists broadened the narrative of the Chicano movement. This book articulates a fresh understanding of how the Chicano movement contributed to the social and political currents of postwar America, and how the movement remains meaningful. --